Double-spraying with different routes significantly improved control efficacies of herbicides applied by unmanned aerial spraying system: A case study with rice herbicides. (May 2023) - Chen, Guo-qi; An, Kai; Chen, Yang; Zhuang, Xiang-xin
Abstract: An unmanned aerial spraying system (UASS) is one of the most important systems for herbicide applications. To date, no study has compared the control efficacies of herbicides applied by UASSs with different application strategies against weeds. We applied post-emergence (POST) herbicides using a six-rotor UASS on rice ( Oryza sativa ) fields with different spraying volumes (22.5, 30, 45, and 60 L ha −1 ) and different spraying route strategies (one-time spraying or two flight sorties routed in length and breadth). The spraying volume significantly affected ( P < 0.05) control efficacies against Echinochloa spp., Leptochloa chinensis, Ammannia baccifera, Monochoria vaginalis, Cyperus difformis, and overall weeds. The spraying route strategy significantly affected control efficacies against Echinochloa spp., Leptochloa chinensis, Ammannia baccifera, and overall weeds. Treatment with the double-spraying strategy significantly increased the control efficacies against Echinochloa spp. and Leptochloa chinensis compared with one-time spraying. For weeds susceptible to herbicides applied, treatments with a spraying volume of 30 L ha −1 showed control efficacies >90%; for grassy weeds, UASS applications with double-spraying routed in length and breadth with a spraying volume of 60 L ha −1 did not show a significant difference with the manual spraying with a spraying volume of 450 L ha −1 in control efficacies. This study revealed different optimal spraying volumes for controlling different groups of rice weeds and demonstrated a new spraying strategy for UASS applications that can be used to improve herbicide application practices with UASSs. Graphical abstract: Image 1 Highlights: Spraying volume significantly affected control efficacies against weeds. Spraying route strategy significantly affected control efficacies against weeds. Double-spraying strategy increased control efficacies against Echinochloa spp. A spraying volume of 30 L ha −1 showed high efficacies against susceptible weeds.